Aufgaben mit Lösung zur Substitution PDF
Document Details
Uploaded by AppreciableSupernova5897
BBZ
Tags
Summary
This PDF contains a set of practice problems on solving equations through substitution. It includes multiple examples where students are expected to solve equations using substitution method. The problems cover basic to intermediate levels of algebra.
Full Transcript
Übungsaufgaben Lösen von Gleichungen mit Substitution 68 Nr Aufgabe Lösung 1 Lösen Sie die Gleichung - 2·x...
Übungsaufgaben Lösen von Gleichungen mit Substitution 68 Nr Aufgabe Lösung 1 Lösen Sie die Gleichung - 2·x 4 + 34·x² – 32 = 0 - 2·x 4 + 34·x² – 32 = 0 ⇔ - 2·z² + 34·z – 32 = 0, Substitution mit x² = z ⇔ z² – 17·z + 16 = 0 ⇔ z² – 17·z + 72,25 = 56,25 ⇔ ( z – 8,5 )² = 56,25 ⇔ z – 8,5 = 7,5 ∨ z – 8,5 = -7,5 ⇔ z = 16 ∨ z = 1 ⇔ x² = 16 ∨ x² = 1 (Rücksubstitution) ⇔ x = 4 ∨ x = -4 ∨ x = 1 ∨ x = -1 2 Lösen Sie die Gleichung - 3·x 4 – 60·x² + 1728 = 0 - 3·x 4 – 60·x² + 1728 = 0 ⇔ - 3·z² – 60·z + 1728 = 0, Substitution mit x² = z ⇔ z² + 20·z - 576 = 0 ⇔ z² + 20·z + 100 = 676 ⇔ ( z + 10 )² = 676 ⇔ z + 10 = 26 ∨ z + 10 = -26 ⇔ z = 16 ∨ z = -36 ⇔ x² = 16 ∨ x² = -36 (unlösbar) (Rücksubstitution) ⇔ x = 4 ∨ x = -4 3 Lösen Sie die Gleichung - 6·x 4 – 30·x² - 24 = 0 - 6·x 4 – 30·x² - 24 = 0 ⇔ - 6·z² – 30·z – 24 = 0, Substitution mit x² = z ⇔ z² + 5·z + 4 = 0 ⇔ z² + 5·z + 6,25 = 2,25 ⇔ ( z + 2,5 )² = 2,25 ⇔ z + 2,5 = 1,5 ∨ z + 2,5 = -1,5 ⇔ z = -1 ∨ z = -4 ⇔ x² = -1 ∨ x² = -4 (Rücksubstitution) unlösbar 4 Lösen Sie die Gleichung - 2·x 4 + 80·x² – 288 = 0 - 2·x 4 + 80·x² – 288 = 0 ⇔ - 2·z² + 80·z – 288 = 0, Substitution mit x² = z ⇔ z² – 40·z + 144 = 0 ⇔ z² – 40·z + 400 = 256 ⇔ ( z – 20 )² = 256 ⇔ z – 20 = 16 ∨ z - 20 = -16 ⇔ z = 36 ∨ z = 4 ⇔ x² = 36 ∨ x² = 4 (Rücksubstitution) ⇔ x = 6 ∨ x = -6 ∨ x = 2 ∨ x = -2 5 Lösen Sie die Gleichung 5·x 4 + 130·x² + 125 = 0 5·x 4 + 130·x² + 125 = 0 ⇔ 5·z² + 130·z + 125 = 0, Substitution mit x² = z ⇔ z² + 26·z + 25 = 0 ⇔ z² + 26·z + 169 = 144 ⇔ ( z + 13 )² = 144 ⇔ z + 13 = 12 ∨ z + 13 = -12 ⇔ z = -1 ∨ z = -25 ⇔ x² = -1 ∨ x² = -25 (Rücksubstitution) F. Mergenthal – www.mathebaustelle.de.de ab_substitution.doc 03.12.101-2 unlösbar 6 Lösen Sie die Gleichung - x 4 + 17·x² – 16 = 0 - x 4 + 17·x² – 16 = 0 ⇔ - z² + 17·z – 16 = 0 , Substitution mit x² = z ⇔ z² – 17·z + 16 = 0 ⇔ z² – 17·z + 72,25 = 56,25 ⇔ ( z – 8,5 )² = 56,25 ⇔ z – 8,5 = 7,5 ∨ z – 8,5 = -7,5 ⇔ z = 16 ∨ z = 1 ⇔ x² = 16 ∨ x² = 1 (Rücksubstitution) x = 4 ∨ x = -4 oder x = 1 ∨ x = -1 7 Lösen Sie die Gleichung 2·x 4 – 64·x² – 288 = 0 2·x 4 - 64·x² – 288 = 0 ⇔ 2·z² – 64·z – 288 = 0, Substitution mit x² = z ⇔ z² – 32·z - 144 = 0 ⇔ z² – 32·z + 256 = 400 ⇔ ( z – 16 )² = 400 ⇔ z – 16 = 20 ∨ z – 16 = -20 ⇔ z = 36 ∨ z = -4 ⇔ x² = 36 ∨ x² = -4 (unlösbar) (Rücksubstitution) ⇔ x = 6 ∨ x = -6 8 Lösen Sie die Gleichung x 4 – 13·x² + 36 = 0 x 4 – 13·x² + 36 = 0 ⇔ z² – 13·z + 36 = 0 ⇔ z² – 13·z + 42,25 = 6,25 ⇔ ( z – 6,5 )² = 6,25 ⇔ z – 6,5 = 2,5 ∨ z – 6,5 = -2,5 ⇔z=9∨z=4 ⇔ x² = 9 ∨ x² = 4 (Rücksubstitution) ⇔ x = 3 ∨ x = -3 ∨ x = 2 ∨ x = -2 9 Lösen Sie die Gleichung - 2·x 4 - 90·x² - 648 = 0 - 2·x 4 – 90·x² – 648 = 0 ⇔ - 2·z² - 90·z - 648 = 0, Substitution mit x² = z ⇔ z² + 45·z + 324 = 0 ⇔ z² + 45·z + 506,25 = 182,25 ⇔ ( z + 22,5 )² = 182,25 ⇔ z + 22,5 = 13,5 ∨ z + 22,5 = -13,5 ⇔ z = -9 ∨ z = -36 ⇔ x² = -9 ∨ x² = -36 (Rücksubstitution) unlösbar 10 Lösen Sie die Gleichung 5·x 4 - 40·x² - 45 = 0 5·x 4 – 40·x² – 45 = 0 ⇔ 5·z² - 40·z – 45 = 0, Substitution mit x² = z ⇔ z² – 8·z – 9 = 0 ⇔ z² – 8·z + 16 = 25 ⇔ ( z – 4 )² = 25 ⇔ z – 4 = 5 ∨ z – 4 = -5 ⇔ z = 9 ∨ z = -1 ⇔ x² = 9 ∨ x² = -1 (unlösbar) ) (Rücksubstitution) ⇔ x = 3 ∨ x = -3 ab_substitution.doc 03.12.102-2